2018
DOI: 10.1186/s13567-018-0567-1
|View full text |Cite
|
Sign up to set email alerts
|

Endonuclease G takes part in AIF-mediated caspase-independent apoptosis in Mycobacterium bovis-infected bovine macrophages

Abstract: Mycobacterium bovis, the causative agent of bovine tuberculosis encodes different virulence mechanisms to survive inside of host cells. One of the possible outcomes in this host–pathogen interaction is cell death. Previous results from our group showed that M. bovis induces a caspase-independent apoptosis in bovine macrophages with the possible participation of apoptosis inducing factor mitochondria associated 1 (AIFM1/AIF), a flavoprotein that functions as a cell-death regulator. However, contribution of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…35 However, whether baicalin could modulate apoptosis via RAGE, MAPK, and AP-1 in PAVECs during H. parasuis invasion has not been investigated. Previous research found apoptosis in monocytes during Streptococcus pneumoniae infection, 36 macrophages infected with Mycobacterium bovis 37,38 or Neisseria gonorrhoeae , 39 and HeLa cells infected by E. coli . 40 Whether PAVECs undergo apoptosis during H. parasuis infection remains unclear.…”
Section: Discussionmentioning
confidence: 93%
“…35 However, whether baicalin could modulate apoptosis via RAGE, MAPK, and AP-1 in PAVECs during H. parasuis invasion has not been investigated. Previous research found apoptosis in monocytes during Streptococcus pneumoniae infection, 36 macrophages infected with Mycobacterium bovis 37,38 or Neisseria gonorrhoeae , 39 and HeLa cells infected by E. coli . 40 Whether PAVECs undergo apoptosis during H. parasuis infection remains unclear.…”
Section: Discussionmentioning
confidence: 93%
“…In the nucleus, AIF activates endogenous nucleic acid endonuclease ( 41 ). AIF-dependent cell death cannot be reduced by caspase inhibitors, suggesting that AIF does not depend on caspases ( 42 ). Under hypoxic conditions, the expression of miR-210-3p in NSCs is upregulated ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Host Bcl-2 protein is the anti-apoptotic one [73]. It counteracts the induction of the intrinsic apoptosis pathway by preventing permeabilization of the outer mitochondrial membrane (OMM) and consequent release of pro-apoptotic molecules, such as cytochrome c [74], apoptosisinducing factor (AIF) [75], endonuclease G (Endo G) [76], and second mitochondria-derived activator of caspase/direct inhibitor of apoptosis-binding (SMAC/DIABLO) protein [77]. BHRF1 shares 38% amino acid sequence homology with human Bcl-2.…”
Section: Bhrf1mentioning
confidence: 99%